Seismic Structural Assessment of the Christchurch Catholic Basilica, New Zealand. (August 2018) - Silva, Luís C.; Mendes, Nuno; Lourenço, Paulo B.; Ingham, Jason
Abstract: An evaluation of the seismic performance of the Christchurch Catholic Basilica, New Zealand, also known as the Cathedral of the Blessed Sacrament, is presented. The cultural importance of the Basilica has been recognised, as it is listed as a Category I building on the New Zealand heritage register. Four strong earthquakes that occurred between September 2010 and June 2011 caused progressive damage and local collapse in the Basilica. Numerical analyses were performed to allow a seismic assessment of the Basilica using the Finite Element Method. A macro-modelling approach following homogenization concepts was considered and the seismic behaviour of the structure was evaluated through pushover analysis with the distribution of forces being proportional to the mass. The analyses allowed damage patterns and capacity curves to be determined, and identified the most vulnerable elements, the maximum load capacity, and the expected collapse mechanisms. Furthermore, a comparison between the numerical output and the existing crack patterns was undertaken, and good agreement was obtained. Finally, two strengthening techniques were evaluated with the aim of reducing the seismic vulnerability of the structure by avoiding collapse of the most vulnerable structural elements.